2017
DOI: 10.1186/s12938-016-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of stent and its dilatation balloon using kriging surrogate model

Abstract: BackgroundAlthough stents have great success of treating cardiovascular disease, it actually undermined by the in-stent restenosis and their long-term fatigue failure. The geometry of stent affects its service performance and ultimately affects its fatigue life. Besides, improper length of balloon leads to transient mechanical injury to the vessel wall and in-stent restenosis. Conventional optimization method of stent and its dilatation balloon by comparing several designs and choosing the best one as the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It was well known that the higher air temperatures in spring and summer were closely related to the low sp and high sund, both of which promoted O 3 formation (Sitnov et al, 2017). Although summer showed the highest air temperature and the longest sunshine duration, the higher rainfall amount in summer decreased the ambient O 3 concentration via wet deposition (Li et al, 2017a(Li et al, , 2019b. Moreover, the highest blh occurred in spring, which was favourable to the strong stratosphere-troposphere exchange process on the Tibetan Plateau (Skerlak et al, 2014).…”
Section: The Temporal Variation In the Simulated 8 H O 3 Concentratiomentioning
confidence: 99%
See 1 more Smart Citation
“…It was well known that the higher air temperatures in spring and summer were closely related to the low sp and high sund, both of which promoted O 3 formation (Sitnov et al, 2017). Although summer showed the highest air temperature and the longest sunshine duration, the higher rainfall amount in summer decreased the ambient O 3 concentration via wet deposition (Li et al, 2017a(Li et al, , 2019b. Moreover, the highest blh occurred in spring, which was favourable to the strong stratosphere-troposphere exchange process on the Tibetan Plateau (Skerlak et al, 2014).…”
Section: The Temporal Variation In the Simulated 8 H O 3 Concentratiomentioning
confidence: 99%
“…Although the STK model incorporated space and time into the model simultaneously, the RF-GAM model outperformed the RF-STK model. It was assumed that the STK model showed higher uncertainty in predicting the O 3 concentration in regions with few sampling sites (Gao et al, 2016;Li et al, 2017a). Overall, the ensemble RF-GAM model showed significant improvement in predictive performance.…”
Section: Model Development and Assessmentmentioning
confidence: 99%
“…where C 10 and C 01 can be obtained by fitting to experimental material properties. In this study, C 10 � 1.0688 MPa and C 01 � 0.771018 MPa [28].…”
Section: Materials Properties Polylactic Acid (Ingeo 4032dmentioning
confidence: 72%
“…However, previous researches mostly focused on studying fatigue resistance of stents in a cylindrical vessel. 17,18,20 Fortunately, more and more researchers have realized that the shape of vessels and plaques will affect the fatigue life of the stent. Cui et al 21 simulated stent expansion in a cylindrical vessel model and a real vessel model.…”
Section: Discussionmentioning
confidence: 99%
“…Their research results indicated that the stent was more prone to fatigue under axial compression than under bending loads. FEA-based sequential quadratic programming method, in combination with Kriging surrogate model, was used by Li et al 20 to analyze and prolong stent's fatigue life. Morlacchi et al 21 studied the effects of calcified plaque, pulsation pressure and cardiac wall movement on the fatigue resistance of stents.…”
Section: Introductionmentioning
confidence: 99%